2016
DOI: 10.1002/chem.201602097
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Observation of Active Conformations in Asymmetric Catalysis: Interaction‐Induced Conformational Preferences of a Chiral Thiourea Model Compound

Abstract: The observation of the active species is the goal of most spectroscopic investigations on enantioselective organocatalysts in solution. Although NMR spectroscopy is widely applied, it has low sensitivity for conformational changes or the chiral nature of the interactions. In the present work, we exemplify the use of vibrational circular dichroism (VCD) spectroscopy for the characterization of a chiral thiourea model compound in nonpolar and polar solvents, as well as for a detailed analysis of its interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 48 publications
(28 reference statements)
2
25
0
1
Order By: Relevance
“…[11] Subsequently,astudy on ac hiral thiourea model compound revealed the advantages of VCD spectroscopyf or studies on intermoleculari nteractions by showing that it can providei nteresting structural insights into the acetate-binding of thioureas. [12] Due to the importance of bifunctional catalysts, we herein investigate reactant binding to TUC by means of VCD spectroscopy.T he actual active conformation in the presence of both reactants, as it is shown in Scheme 1, is difficult to study though, as the simultaneous binding of the reactants will lead to an immediate and fast reaction and thus ag enerally low concentration of the active complex. Therefore, we focus on carboxylic acids as model substrates, which presumably interact simultaneously with both binding sites of TUC without initiating ar eaction.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Subsequently,astudy on ac hiral thiourea model compound revealed the advantages of VCD spectroscopyf or studies on intermoleculari nteractions by showing that it can providei nteresting structural insights into the acetate-binding of thioureas. [12] Due to the importance of bifunctional catalysts, we herein investigate reactant binding to TUC by means of VCD spectroscopy.T he actual active conformation in the presence of both reactants, as it is shown in Scheme 1, is difficult to study though, as the simultaneous binding of the reactants will lead to an immediate and fast reaction and thus ag enerally low concentration of the active complex. Therefore, we focus on carboxylic acids as model substrates, which presumably interact simultaneously with both binding sites of TUC without initiating ar eaction.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the combination of stereochemical sensitivity with the rich structural content of vibrational spectra by VCD and Raman Optical Activity (ROA) has brought forward very reliable approaches for the AC determination of natural products [ 16 , 17 ]. In addition, the conformational sensitivity of vibrational spectroscopy allowed some insights into very interesting conformational variations in natural products [ 18 ] as well as peptides and other chiral molecules [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced from ref. [31] In Figure 3b, we show a comparison of the experimental IR and VCD spectra of pure 12 and those computed at B3LYP/6-311+G(2d,p)/IEFPCM(CHCl 3 ) level of DFT. The basis for the spectra predictions was a comprehensive conformational analysis that pointed to a trans-conformation of the thiourea moiety as energetically most favorable structure (cf.…”
Section: Hydrogen Bonding Interactions In Thiourea Catalysismentioning
confidence: 99%
“…Reproduced from ref. [31] plex structure shown in Scheme 3, with bifurcated hydrogen bonding pattern between thiourea and acetate and an additional hydrogen bond between acetate and solvent. We showed that this bifurcated structure must significantly contribute to the conformational equilibrium.…”
Section: Hydrogen Bonding Interactions In Thiourea Catalysismentioning
confidence: 99%
See 1 more Smart Citation